Synthesis and in vitro evaluation of tetrazole containing 1,5-benzothiazepines as new anticancer, antitubercular, antibacterial, and antifungal agents - Suman, Ashok Kumar; Anu, Anu; Singh, Bhawani (European Journal of Chemistry, 2024)
Heterocyclic scaffolds have attracted great attention of organic chemists and medicinal chemists, also because of their wide range of synthetic applicability and broad spectrum of biological profile. Therefore, in the present research work, a series of tetrazole containing 1,5-benzothiazepines have been synthesized for evaluation of their biological activities to determine the potential therapeutic profile of these compounds across various medicinal domains. Of the synthesized compounds, five compounds (6f, 8e, 8f, 8g, and 8h) have been screened for anticancer, antitubercular, antibacterial, and antifungal activities. After evaluation of these biological activities, it was found that these compounds possess very limited anticancer activity, moderate antibacterial and antifungal activity, and very strong antitubercular activity, which indicate their great pharmacological applications as subjects for future investigations of novel therapeutic agents for the treatment of tuberculosis.